„Poznaj samego siebie” w interpretacji Bazylego Wielkiego - Osek, Ewa (Vox Patrum, 2008)
There are some references to the famous Delphic inscription „Know thyself” (gnothi sauton) in the Hexaemeron (IX 6; VI 1) and the Homilia in illud: Attende tibi ipsi by St. Basil of Caesarea. In the Homilia in illud: Attende tibi ipsi St. Basil accepts the Philo’s and Clement of Alexandria’s opinion that the Septuagint proseche seauto („Attend to yourself”) and the Hellenie gnothi sauton („Know thyself”) are the same. According to St. Basil, influenced by the Alcibiades I, „yourself” means „a soul” as an opposite to a body and its environment. St. Basil interprets the Delphic maxim in the following meanings: (1) „Turn to yourself”, (2) „Know God from yourself”, (3) „Take care of your soul”, (4) „Control yourself”, and (5) „Remember you are a human”. His interpretation is influenced by the many philosophical writings, especially the Platonie dialogues (the Charmides, the Alcibiades I), the Stromata of Clement of Alexandria, and the Origen’s In Canticum canticorum.